Right or Flawed: Relationship Obsessions and Sexual Satisfaction. (1st September 2014) - Doron, Guy; Mizrahi, Moran; Szepsenwol, Ohad; Derby, Danny
Abstract: Introduction: Relationship obsessive–compulsive disorder (ROCD) is marked by the presence of obsessions and compulsions focusing on romantic relationships. ROCD symptoms were previously linked with decreased relationship quality and might interfere with sexual functioning. Aim: The study aims to examine the association between ROCD symptoms and sexual satisfaction. Methods: Participants completed an online survey assessing ROCD symptoms and relationship and sexual satisfaction levels. Depression, general worry, obsessive–compulsive disorder (OCD) symptoms, and attachment orientation were also measured. Main Outcome Measure: The main outcome measures were self reported relationship satisfaction and sexual satisfaction. Results: ROCD symptoms were associated with decreased sexual satisfaction over and above symptoms of depression, general worry, OCD, and attachment orientation. The link between ROCD symptoms and sexual satisfaction was mediated by relationship satisfaction. Conclusions: Identifying and addressing ROCD symptoms may be important for treatment of sexual functioning.